When Reality and Research Collide: Guidelines Are Essential for Optimal Nutrition Care in Pediatric Oncology. Issue 1 (January 2022) - Ringwald-Smith, Karen; Hill, Rachel; Evanoff, Lisa; Martin, Jenna; Sacks, Nancy
Abstract : Nutritional problems are common in pediatric oncology due to the side effects of the disease and treatment. Nutrition intervention can be challenging, and little is known about the current clinical practice of registered dietitian nutritionists. An online questionnaire emailed to members of the pediatric, oncology nutrition, and clinical manager practice groups of the Academy of Nutrition and Dietetics, consisted of items related to current nutrition practice. Our questionnaire results suggest that the field of pediatric oncology is employed with relatively new dietitians (62% had <5 y of experience). Many registered dietitian nutritionists (60%) are providing care across the cancer care continuum (standard therapy, transplant, and survivorship) versus specializing in a particular area. Approximately half (52%) felt that their center had inadequate staffing, many reporting little in the outpatient setting. Barriers to providing optimal patient care included inadequate staffing, lack of time for research initiatives, and lack of evidence-based guidelines. Future studies should determine follow-up guidelines and appropriate staffing ratios for nutrition care in pediatric oncology. Approaches should be developed to support less experienced dietitians. Collaboration between dietitians at different facilities will likely be key in developing essential evidence-informed guidelines.